Précipitations intenses sur le Bassin Méditerranéen : quelles tendances entre 1950 et 2013 ? - Florian Raymond; Albin Ullmann; Pierre Camberlin (Cybergeo, 2016)
The main objective of this study is to characterize Mediterranean rainfall spatiotemporal features from 1950 to 2013, with a focus on intense events. Results show a general decrease in precipitation amounts during the September to April period. The Mediterranean Basin also shows a strong decrease in the number of rainy days in northern Portugal, Algeria, northeast Anatolia, in southern Balkans and in almost all of Italy. In the current context of global warming, changes in intense Mediterranean precipitation events remain less obvious, with no significant evolutions in the number and intensities of such events. Only few zones such as southwest Anatolia, eastern Balkans and parts of the Iberian Peninsula, show an increase in the contribution of intense rainfall in the total precipitation amount over the 1950-2013 period.